A Nascent Look at Theoretical Frameworks in Middle Level Education Research - Cynthia Reyes; Steven Netcoh (Middle Grades Review, 2015)
This paper describes a qualitative content analysis of research articles published on middle level education in the last decade. This analysis was conducted on manuscripts appearing in two premier middle level education journals: Middle Grades Research Journal (MGRJ) and Research in Middle Level Education Online (RMLE) to explore the following questions: 1) What theoretical frameworks are being used in middle level education research?; and 2) How are the theoretical frameworks specific to the field of middle level education, and/or how are they borrowed from other disciplines? The findings depict how authors of research articles have applied theories from other broader disciplines. Echoing the recommendation of Bickmore and colleagues (2003) to address both theory and practice in single research articles, the authors suggest a more nuanced and in-depth look at how knowledge is constructed in the middle grades field.